ELEMENTS THAT REVEAL THE PHONETIC AND PHONOLOGICAL PROPERTIES OF ARTISTIC WORKS (USING EXAMPLES FROM TOG‘AY MURAD’S WORKS) (Academicia Globe: Inderscience Research, 2022)
The ability to express the rules of methodical use of sounds in writing is limited. However, pronunciation and narrative compatibility can be achieved using phonographic tools. In the work of art, the inner excitement of the protagonists in the psyche, joy, sadness, consent, surprise, begging, amazement, sarcasm, pitching, cutting, applause, questioning, emphasis, dissatisfaction, protest, wish, etc. In conveying situations such as support to the reader, writers use more than one phonographic method of writing vowels or consonants. Uncle Murad's work seeks to illustrate the effective and appropriate use of these elements through real-life examples.